Outcome of back pain and radiculopathy in patients with single level lumbar discectomy - Muhammed Saeed, Sherzad; Snear Dri , Rekib (Diyala Journal of Medicine, 2023)
Background: Surgery for lumbar disc herniation is one of the most commonly performed procedures in spine surgery. Questions remain if lumbar discectomy is the optimal treatment for patients with lumbar disc herniation who exhibit a substantial amount of preoperative back pain. Objective: To evaluate the outcome of improvement of back pain and radiculopathy between male and female patients with single-level discectomy and in relation to different indications for the surgery. Patients and Methods: In this retrospective follow-up study, 80 patients (40males and 40 females) with symptoms of radiculopathy and back pain who underwent single-level open discectomy (small incision of 2-3 cm) were followed-up by discharge from the hospital between 2017 and 2019 in Erbil, Iraqi Kurdistan. The patients were included after having the symptoms of radiculopathy as confirmed on magnetic resonance imaging. In addition, patients who had undergone discectomy due to radiculopathy without response after 6 weeks of conservative treatment were included in this investigation. Results: The mean age of the patients was 45.1 (19-70 years old). The study showed that the level of back pain and radicular pain was significantly decreased from the initial step to 3, 6, and 12 months. The levels of back and radicular were not changed significantly from three to six months. The study showed that the prevalence of different levels of back and radicular pain was similar between male and female patients at different periods. The study did not find a significant difference in levels of back and radicular pains among patients with different indications in male and male patients. Conclusion: This study showed that single-level lumbar discectomy improved back and radicular pain by 12 months postoperatively in males and females, regardless of the indication for surgery.